Performance investigations of internet protocol versions for mobile Ad-hoc network based on qualnet simulator - Jaber H. Majeed; Najmah Abed Habeeb; Waleed Khalid Al-Azzawi (Indonesian Journal of Electrical Engineering and Computer Science, 2021)
A mobile ad hoc network (MANET) can be seen as a mobile nodes collection having no support of fixed infrastructure and therefore its communication is totally dependent on the network's nodes. As a result of the mobility of nodes, rapid and unpredictable changes occur within the mobile ad hoc network (MANET) arrangements. Therefore, this makes the analysis of routing protocols very crucial so as to enhance efficient communication between the wireless nodes. IPv4 and IpV6 within the MANET is another issue of concern. IPv4 which has been traditionally used for ages and IPv6; predicted to be the forthcoming network architecture model is investigated because of its protection which has been improved as well as its enormous address space provision. The analysis on Ad Hoc On Demand Vector and Dynamic Manet On Demand routing protocols are performed using Qualnet simulator under the IPv4 and IPv6 standards. A thorough evaluation of the usability and functionality of the simulator software is carried out. The metrics for performance are; Throughput, End-to-End Delay and Average jitter. Afterwards, analyses and summary of the results is conducted and summarized in order to make available an assessment of their performances.